PENGEMBANGAN DAN PENINGKATAN KINERJA PAMONG BELAJAR SANGGAR KEGIATAN BELAJAR - Hapsari, Melati Indri (JIV-Jurnal Ilmiah Visi, 2008)
The success of a Learning Activity Center much depends on the tutors’ competence and creativity. This articles discusses some variables influencing the tutors’ performance and puts forward a number of suggestions to improve the tutors’ performance.